Exploring the potential value of SRC in pan cancer based on bioinformatics methods - Liyin Huang; Yanwen Lu; Lei Yi; Yuxin Zhao; Tao Si; Mingmin Zhang (Discover Oncology)
Abstract Background Tyrosine-Protein Kinase Src (SRC), a non-receptor tyrosine kinase encoded by the Src gene, plays a crucial role in cell growth, division, migration, and survival signaling pathways. Dysregulation of SRC expression and activity is associated with advanced stages of several human cancers and poor prognosis. However, the prognostic value of SRC across multiple cancers and its involvement in immune response remain unclear. Therefore, this study aimed to investigate the relationship between SRC expression levels and cancer patient prognosis, as well as its potential impact on the immune microenvironment. Methods In this study, we utilized the Sangerbox database to investigate the differential expression of SRC in various types of cancer tumors and adjacent normal tissues. Survival outcomes of SRC expression levels in pan cancer were analyzed by Cox risk ratio and Kaplan Meier analysis. We further explored the relationship between SRC expression and immune regulatory genes, tumor mutation load, microsatellite instability, and the immune microenvironment of pan cancer using the Sangerbox database. Results Compared to normal tissues, SRC expression is upregulated in various tumor tissues. SRC is significantly correlated with OS and in tumors such as LIHC and PRAD. Furthermore, SRC expression is significantly associated with mutation burden and microsatellite instability in tumors such as LUAD and COAD. In addition, SRC expression is related to the abundance of infiltrating immune cells in tumors such as LIHC and PRAD. These findings suggest that SRC may serve as a potential prognostic biomarker and therapeutic target for various cancers, and may be associated with the immune microenvironment of tumors. Conclusion Our results suggest that SRC may play a role in regulating immune infiltration and impacting the prognosis of cancer patients, highlighting its potential as a therapeutic target and biomarker for various cancers.